Increasing Motivation and Achievement in Learning English of eleven grader Science-3 Students of State Senior High School 5 Magelang using Problem Based Learning - Siswidyatmi Siswidyatmi; Lilia Indriani; Setiyo Prajoko (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This study aims to determine the increase in motivation and  achievement in learning English for eleven grader students of Science 3  Class,  State Senior High School 5 Magelang  using Problem-Based  Learning. The classroom action research method  used in this study  began at the pre-cycle , cycle 1, and cycle 2 stage. Pre-cycle stage  is used to obtain the initial data on the condition of the students before using problem based learning. While cycle 1 and cycle 2 learning were carried out with problem based learning. At each stage data collection is carried out for learning achievement  in both knowledge and skills and motivation to learn using test  and questionnaires. The results of the study has increased  the average learning motivation of 0.18 both in the pre-cycle to cycle 1 and cycle 1 to cycle 2. An increase in knowledge aspect competence  by 56% occurred in pre-cycle to cycle 1 and 20% in cycle 1 and cycle 2. For skill aspects there is an increase of an average of 1 both at the pre-cycle to cycle 1 and cycle 1 to cycle 2. It can be concluded that Problem Based Learning is able to increase students’ motivation and learning achievement.